On graphs with the smallest eigenvalue at least -1- square root 2, part II - Taniguchi, Tetsuji (Ars mathematica contemporanea, 2012)
This is a continuation of the article with the same title. In this paper, the family ?$\mathscr{H}$? is the same as in the previous paper T. Taniguchi, On graphs with the smallest eigenvalue at least ?$-1 - \sqrt{2}$?, part I, Ars Math. Contemp 1 (2008), 81-98. The main result is that a minimal graph which is not an ?$\mathscr{H}$?-line graph, is just isomorphic to one of the 38 graphsfound by computer.
Keywords: generalized line graph; matematika; mathematics; posplošeni povezavni grafi; spectrum; spekter; teorija grafov